Red Cell Folate, Serum Vitamin B12 and Ferritin Levels During Pregnancy and their Correlation with Red Cell Indices - Saba Kazmi (Journal of Rawalpindi Medical College, 2013)
Background: To determine serum ferritin, red cell folate and serum vitamin B12 levels in pregnant women and their correlation with red cell indices. Methods: In this cross sectional study venous blood samples of a total of 60 pregnant women were included and their haematological and biochemical parameters were determined including blood complete picture, serum ferritin, serum vitamin B12 and Red Cell Folate. Results: Mean ± SD age of the subjects was 29 ± 5 with a range of 20 to 40 yrs. Majority of patients had mixed deficiency anaemia which suggested that serum ferritin, serum vitamin B12 and red cell folate can help in identifying patients of mixed deficiency anaemia. Conclusion: Pregnant women with normal MCV should be screened for mixed deficiency anemia. Iron deficiency is associated with a low Mean Corpuscular Volume (MCV). On the other hand Vitamin B12 and folate deficiency is associated with a raised MCV. In pregnant women with concomitant iron and Vitamin B12/ Folate deficiencies a normal MCV might not be a reliable index.